THE PROJECT OF IMMORTALITY IN POETRY - Masulah . (Universitas Muhammadiyah Surabaya, 2007)
ABSTRACTThe perennial problem for human beings is loss and decay. Life is fragile and transient and Death is as close as life. However, when man dies, as everyone must admit they eventually do, do they really extinct, that is,do they stay dead forever? Or as Job phrases it, “If a man dies, shall he live again?” There can be no doubt that the threat of mortality and the possibility of immortality have been always the foremost incentives to philosophical inquiry. It was Socrates who ascribes philosophyas basically a “meditation on death”, a meditation on whether man is mortal or immortal. This paper will examine how poetry mediates about the problem of death (mortality) and the prospect of immortality as explored by Allan Tate in Ode to the Confederate Dead and John Keats in Ode to Nightingale and To Autumn. This paper will be starting with general overview of immortality in poetics. The Introductory section will address such questions as: How do human beings conceive theimmortality of their existence through out the history? How do lyrics deal with the issue of immortality? What image does lyric try to preserve? How do some lyrics differ in their conceptions toward loss, decay, and death?Allan Grossman’s Summa Lyrica is used as the starting point of the discussion. This section will review Grossman’s guidelines on the dynamics of the poets and their creation: How a poet monumentalizes thepersona and the voice through his creation and how his whole creation in turn creates a legendary figure of himself as a human being and as a poet, remembered and celebrated by the world. Further discussion will be focusing on Keats’ To Autumn, and Ode to Nightingale, and Tate’s Ode to the Confederate Dead. The discussion on these odes will address the issue of the media through which Death can be the agent of immortalityrather than the menacing power of mortality.